2017
DOI: 10.1007/978-981-10-5987-2_6
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasomes in the Gut Mucosal Homeostasis

Abstract: Inflammasomes are critical checkpoints in inflammation. The activation of inflammasome can cause a series of inflammatory responses including maturation of interleukin (IL)-1β and IL-18 and a specialized form of cell death called pyroptosis. Since its identification in the early 2000s, inflammasomes have been implicated to play multifaceted roles in varied pathological and physiological conditions, especially in the mucosal compartments including the gut. Maintaining gut mucosal homeostasis has always been a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 113 publications
0
6
0
1
Order By: Relevance
“…In this study, we have shown for the first time that C. sakazakii not only induces apoptosis but also elicits pyroptosis, triggered by caspase-1 activation via inflammasomes (39). The premature human gut is notable for displaying increased expression of various proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this study, we have shown for the first time that C. sakazakii not only induces apoptosis but also elicits pyroptosis, triggered by caspase-1 activation via inflammasomes (39). The premature human gut is notable for displaying increased expression of various proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 96%
“…Inflammatory responses are activated by inflammasomes (multiprotein oligomers), which are responsible for a more robust immune response to microbial pathogens and which promote the activation/maturation of inflammatory caspase-1 and proinflammatory cytokines such as IL-1β (39). Proteus mirabilis, through the NLRP3 inflammasome, can contribute to dextran sulfate sodium-induced colitis, indicating that disease outcomes are affected by the various commensal microbiota present in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Although physiological inflammation was beneficial to the intestine, overwhelming inflammatory microenvironment and excessive inflammatory cytokines can ultimately prompt colonic tumorigenesis [29,30]. As a critical initiator of inflammation, NLRP3 inflammasomes play a critical role in regulating the inflammatory microenvironment by inflecting innate immune responses, recruiting immunocytes, mediating cell deaths, and stabilizing gut microbiota [31,32]. The specific effect varies with the signal pathways involved.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27] In addition, while it appears that there have been correlations noted between the microbiome of the gut and inflammasome activation, solid links between the skin microbiome and inflammasome activation or suppression are lacking. 28,29 The activated nod-like receptor proteins, or NLRPs, create circular Inflammasome oligomers, Figure 1. The NLRPs are comprised of three key molecular components that include 1) Nucleotide-binding domain and Leucinerich repeat Receptors (NLR), 2) Apoptosis-associated Speck-like protein (ASC), and 3) inactive Caspase-1 (Pro-Caspase-1).…”
Section: Introductionmentioning
confidence: 99%